Bird communities in tropical rain forest - Rosli, Zamri; Hussin, Mohamed Zakaria (Lambert Academic Publishing, 2015)
This book is published to view what is happened to the understorey birds before and immediately after logging in a tropical rain forest of Malaysia. Some study predict that some species of the understorey birds will declining following logging activities while some increased. The findings from this study can be used to provide information and serve as a guide for further studies on the effects of the understorey bird species in the tropical rain forest.